Aesthetics of the Babuai Dance and the Transformation of Tradition at the Singo Barantai Traditional Arts Institute, Padang - Yosi Nofa; Yuliarni Yuliarni; Afrizal Harun; Asril Asril; Dede Pramayoza (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2025)
Babuai dance is one of the traditional Minangkabau dances that developed at the Singo Barantai Padang Traditional Arts School. This dance is one of the unique traditional dances. Because the movements of this dance depict agility, softness, firmness and sharpness. In every movement is full of accents (movement jerks) besides that there is also acceleration and deceleration. This dance is used for body exercise for a silat athlete before they carry out silat training. The object of this research uses Dance as its formal object, "Babuai Dance" as its material object. This research uses a qualitative method with a descriptive analytical approach. This research was conducted at a silat school, namely the Singo Barantai Padang City Traditional Arts School, which is located in Lubuk Leetah, Kuranji District, Padang. Singo Barantai Traditional Arts College is one of the non-formal educational institutions engaged in the field of arts and culture, where the activities or materials taught at this College include traditional martial arts with the SilekPauh flow, randai, traditional dance, traditional Minangkabau music, and traditional pasambahan speeches. This journal examines the tradition of challenging change in the study of dance aesthetics. Babuai dance is viewed using aesthetic studies with the aim of revealing and exploring in depth everything related to the beauty of the Babuai Dance and changes in the development of the babuai dance at the Singo Barantai Traditional Arts College. In this study, the author was actively involved in the Singo Barantai Traditional Arts College, namely as a participant observer, which means that the author directly enters and is involved in the membership of the Singo Barantai College